Mobilization of nonconjugative antibiotic resistance plasmids in Haemophilus ducreyi. - Deneer, H G (1982)
A clinical isolate of Haemophilus ducreyi was found to harbor three plasmids: a 23.5-megadalton (Mdal) phenotypically cryptic plasmid, a 7.0-Mdal ampicillin resistance plasmid, and a 4.0-Mdal sulfonamide resistance plasmid. The two smaller plasmids were transferable by conjugation to Haemophilus recipients, but only if the donor cell harbored the 23.5-Mdal plasmid as well, indicating that this large plasmid had mobilizing capabilities. Transfer was also possible to Escherichia coli recipients. Haemophilus influenzae transconjugants which had acquired both the 23.5-Mdal plasmid and one of the R-plasmids could subsequently retransfer the R-plasmid to other Haemophilus recipients at higher frequencies. A derivative of the 23.5 Mdal plasmid was isolated which was shown by restriction endonuclease analysis to contain an ampicillin resistance transposon and to have retained its conjugative ability.